Virtual teaching assistant for capturing facial and pose landmarks of the students in the classroom using deep learning - Roznim Mohamad Rasli (Tanjung Malim, 2023)
Virtual teaching assistant for capturing facial and pose landmarks of the students in the classroom using deep learning by Roznim Mohamad Rasli